Workshop Teknik Penyusunan Instrumen Penelitian Guna Peningkatan Kualitas Dan Percepatan Penyelesaian Skripsi Mahasiswa - Hasnawati; Nisa, Khairun; Novitasari, Setiani; Putri, Hikmah Ramdhani; Hera Sukmawati (Universitas Mataram, 2025)
Research instruments are an important element in the process of collecting valid and reliable data. Errors in instrument preparation can affect the quality of data and research results. Therefore, students need to understand the techniques of compiling research instruments well. However, many students still do not understand how to compile good instruments and experience many technical obstacles in compiling these instruments. Therefore, based on this, it is important to hold a workshop on research instrument preparation techniques to improve the quality and accelerate the completion of student theses, as one of the initial steps to improve the quality of theses or final assignments that will be produced by students and accelerate the completion of theses. The stages in this workshop activity are through 4 stages: first, coordination, second, promotion, third, implementation, and fourth, evaluation and reporting. This workshop activity was held in room F17, campus 2, FKIP, University of Mataram on Saturday, August 23, 2025. During the implementation of the activity, at the beginning, a pre-test was carried out, then continued with the presentation of material and discussion and ended with a post-test and filling out a participant response questionnaire. Based on the results of the pretest and posttest, it was seen that there was an increase in the understanding of the students participating in the workshop regarding the techniques for preparing research instruments in general and based on the results of the participant response questionnaire regarding the workshop activities carried out, on average the students gave a positive response